Nox (NADPH Oxidase) 1, Nox4, and Nox5 Promote Vascular Permeability and Neovascularization in Retinopathy. Issue 4 (April 2020) - Deliyanti, Devy; Alrashdi, Saeed F.; Touyz, Rhian M.; Kennedy, Christopher R.; Jha, Jay C.; Cooper, Mark E.; Jandeleit-Dahm, Karin A.; Wilkinson-Berka, Jennifer L.
Abstract : Hypertension is a risk factor for the vascular permeability and neovascularization that threatens vision in diabetic retinopathy. Excess reactive oxygen species derived from the Nox (NADPH oxidase) isoforms, Nox1 and Nox4, contributes to vasculopathy in diabetic retinopathy; however, if Nox1/4 inhibition is beneficial in hypertensive diabetic retinopathy is unknown. Here, we determined that diabetic spontaneously hypertensive rats had exacerbated retinal vascular permeability and expression of angiogenic and inflammatory factors, compared with normotensive diabetic Wistar Kyoto rats. GKT136901, a specific dual inhibitor of Nox1 and Nox4, prevented these events in diabetic Wistar Kyoto rats and spontaneously hypertensive rats. Retinal neovascularization does not develop in diabetic rodents, and therefore, the oxygen-induced retinopathy model is used to evaluate this pathology. We previously demonstrated that Nox1/4 inhibition reduced retinal neovascularization in oxygen-induced retinopathy. However, although Nox5 is expressed in human retina, its contribution to retinopathy has not been studied in vivo, largely due to its absence from the rodent genome. We generated transgenic mice with inducible human Nox5 expressed in endothelial cells (vascular endothelial-cadherin + Nox5 + mice). In vascular endothelial-cadherin + Nox5 + mice with oxygen-induced retinopathy, retinal vascular permeability and neovascularization, as well as the expression of angiogenic and inflammatory factors, were increased compared with wild-type littermates. In bovine retinal endothelial cells, which express Nox1, Nox4, and Nox5, Nox1/4 inhibition, as well as Nox5 silencing RNA, reduced the high glucose–induced upregulation of oxidative stress, angiogenic, and inflammatory factors. Collectively, these data indicate the potential of Nox1, Nox4, and Nox5 inhibition to reduce vision-threatening damage to the retinal vasculature. Abstract : Supplemental Digital Content is available in the text.